Improving The Preparation Of Future Primary School Teachers By Developing Education - Sultanova U. M. (Euro Asian Journal Publishing, 2024)
The article emphasizes the importance of developmental education in the training of future primary school teachers in the higher education system, as a means of social and pedagogical influence on teacher training.
Keywords: education; developmental learning; future primary school teacher